2012
DOI: 10.1007/978-3-642-30609-9_8
|View full text |Cite
|
Sign up to set email alerts
|

Forward Kinematic Modelling of a Regional Transect in the Northern Emirates Using Geological and Apatite Fission Track Age Constraints on Paleo-Burial History

Abstract: This paper aims to simulate the kinematic evolution of a regional transect crossing the Northern Emirates in the northernmost part of the Semail Ophiolite and the Dibba zone, just south of the Musandam Platform exposures. The studied section comprises, from top to bottom and from inner to outer zones, (1) the erosional remnants of the Semail Ophiolite, mainly made up of serpentinized ultramafics in the west and gabbros in the east, (2) high-grade metamorphic rocks which are currently exposed in the core of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 14 publications
4
45
0
Order By: Relevance
“…Other thrusts imaged on the seismic sections cut through the subophiolite sheets and the shelf carbonates, but it is uncertain if these are late-stage ophiolite emplacement-related Late Cretaceous thrusts or mid-Cenozoic (Musandam type) thrusts associated with the initial continental collision. The east-dipping normal fault bounding the southeast margin of Musandam and the northwest margin of the Dibba zone (Searle, 1988a(Searle, , 1988bSearle et al, 2014) is shown clearly in the interpretative sections of Tarapoanca et al (2010;Fig. 4).…”
Section: Deep Seismic Constraints From the Uaementioning
confidence: 97%
See 3 more Smart Citations
“…Other thrusts imaged on the seismic sections cut through the subophiolite sheets and the shelf carbonates, but it is uncertain if these are late-stage ophiolite emplacement-related Late Cretaceous thrusts or mid-Cenozoic (Musandam type) thrusts associated with the initial continental collision. The east-dipping normal fault bounding the southeast margin of Musandam and the northwest margin of the Dibba zone (Searle, 1988a(Searle, , 1988bSearle et al, 2014) is shown clearly in the interpretative sections of Tarapoanca et al (2010;Fig. 4).…”
Section: Deep Seismic Constraints From the Uaementioning
confidence: 97%
“…We use our structural mapping constraints to restore the Bani Hamid thrust sheet in relation to the known geometry of the Semail ophiolite thrust sheet and present a tectonic evolution based on our new data combined with U-Pb timing constraints (Styles et al, 2006;Rioux et al, 2012aRioux et al, , 2013. We speculate on the composition and structure of the lower crust as imaged on recently acquired deep seismic profiles across the mountains in northern Oman and the UAE (Rouré et al, 2006;Tarapoanca et al, 2010;Naville et al, 2010). We integrate geological constraints from the northeastern Oman mountains where high-pressure eclogites have been exhumed east of Muscat (As Sifah eclogites; Searle et al, 1994Searle et al, , 2004Warren et al, 2003;Agard et al, 2010), and from the northern mountains where the Bani Hamid granulites crop out, to formulate a model for ophiolite obduction and emplacement.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…9) shows deep-seated high-angle thrusts that can be traced down into the Mesozoic platform sequence which have restacked the platform and overlying Suneinah and Pabdeh foredeep deposits with a westward sense of movement. These increases in intensity to the north towards the Musandam culmination, where they involve thick-skinned imbrication of the whole of the shelf sequence (Dunne et al 1990;Tarapoanca et al 2010), die out to the south and are absent from the Jabal Qumayrah profile (Fig. 10).…”
Section: Post-emplacement Latest Cretaceous and Cenozoic Overprintingmentioning
confidence: 99%